How to explore ambient electrocatalytic nitrogen reduction reliably and insightfully. (20th May 2019) - Tang, Cheng; Qiao, Shi-Zhang
Abstract : A guidebook with best practices and potential opportunities to explore ambient electrocatalytic nitrogen reduction reliably and insightfully. Abstract : The efficient activation of dinitrogen for the production of ammonia plays a crucial role in our modern society, considering the significant impact of ammonia on food, chemicals, and energy. As an attractive alternative to the century-old Haber–Bosch process which is responsible for 1–2% of global energy consumption, utilization of half the hydrogen produced globally, and ∼1% of global energy-related CO2 emissions, the ambient electrocatalytic nitrogen reduction reaction has attracted tremendous interest during the past few years. Some achievements have revealed the possibility of this process, but have also identified great challenges. The activity and selectivity of the nitrogen reduction reaction are fundamentally limited by competing hydrogen evolution and nitrogen scaling relations, while low production rates and ubiquitous contaminants plague experimental practices. Aiming toward higher accuracy and reproducibility of claimed results, and more meaningful, impactful, and insightful research, this tutorial review summarizes the present status and challenges in the study of ambient electrocatalytic nitrogen reduction, followed by a thorough discussion of various experimental parameters. We then recommend a series of protocols and best practices for experiments, and also highlight some potential directions for future research in this exciting and important field.